Do open journals get cited more in government policy? - Adie, Euan (Septentrio Conference Series, 2020)
See RECORDING (starts at 00:21:34). There's a clear - if not completely understood - download and citation advantage for open access articles. We investigate whether or not this holds true for citations outside of the scholarly literature, specifically for references to scholarly work in government white papers, guidelines and other policy documents. Does making an article more available mean that it's more likely to have a policy impact? We follow up with a list of strategies different journals and publishers have adopted to make sure that the research they publish reach the right policymakers at the right time, as well as a brief discussion on the role of preprints and review articles.